Topical therapy for refractory rhinosinusitis caused by methicillin-resistant Staphylococcus aureus: First report in a prospective series. Issue 5 (October 2018) - Shikani, Alan H.; Khoueir, Nadim; Jabra-Rizk, Mary Ann; Shikani, Henry J.; Basaraba, Randall J.; Leid, Jeff G.
Abstract: Objective: The incidence of refractory chronic rhinosinusitis (CRS) associated with methicillin-resistant Staphylococcus aureus (MRSA) is rising and remains a therapeutic challenge. The goal of this study is to demonstrate the efficacy of a non-invasive topical therapy against MRSA in these patients. Methods: Seventeen patients with refractory CRS caused by MRSA were treated with a topical therapy protocol. Treatment consisted of weekly endoscopic sinus debridement followed by intra-sinus installation of a hydroxyl-ethylcellulose gel that releases mometasone and a culture-directed antibiotic for a period of 6 weeks, along with daily nasal nebulization of mometasone with the same antibiotic and saline rinses. Clinical outcome was assessed using the Lund–Kennedy (LK) symptom and endoscopic appearance scores. Sinus mucosal tissue was homogenized and cultured, and microbial biofilm burden was assessed based on colony forming units (CFUs) counts. Results: Rhinotopic therapy resulted in clearance of MRSA in 13 of 16 patients (81.2%). Treated patients also demonstrated significant improvement clinically as measured by the LK scores. In addition, a significant decrease in mucosal CFUs was observed post-therapy. Conclusion: Our findings demonstrate that topical therapy is an effective method for treating MRSA-associated refractory CRS.